1995
DOI: 10.1164/ajrccm/151.4.1040
|View full text |Cite
|
Sign up to set email alerts
|

Release of [3H]Acetylcholine in Human Isolated Bronchi: Effect of Indomethacin on Muscarinic Autoinhibition

Abstract: Receptor-mediated regulation of acetylcholine release in the airways, particularly in humans, remains unclear. In the present study, the tissue content of acetylcholine and release of [3H]acetylcholine were measured in freshly dissected human bronchi obtained at thoracotomy. Large (main and lobar bronchi) and small (segmental and subsegmental bronchi) airways contained considerable amounts of endogenous acetylcholine (300 +/- 50 pmol/100 mg wet weight), whereas significantly less was found in lung parenchyma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…2007). However, observation that ACh is synthesized and released by the bronchial epithelium has been known since 1995 (Wessler et al . 1995), then Maus et al .…”
Section: Introductionmentioning
confidence: 99%
“…2007). However, observation that ACh is synthesized and released by the bronchial epithelium has been known since 1995 (Wessler et al . 1995), then Maus et al .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of endogenous ACh was performed as described previously by cationic exchange HPLC with electrochemical detection [Wessler et al, 1995;Reinheimer et al, 1996;Klapproth et al, 1997]. In brief, cultured cells were first detached by trypsinisation and counted using a Neubauer counting chamber.…”
Section: Detection Of Achmentioning
confidence: 99%
“…In nonasthmatic humans it has been demonstrated that the neuronal M 2 muscarinic receptor is not dependent upon prostaglandins (46). However, it is tempting to speculate that in aspirin-sensitive asthma previous exposure to inflammatory mediators at some critical period has altered coupling of the neuronal M 2 muscarinic receptor to cyclooxygenase.…”
Section: Discussionmentioning
confidence: 99%